1994
DOI: 10.1523/jneurosci.14-01-00140.1994
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hair cell progenitors and intermitotic migration of their nuclei in the normal and regenerating avian inner ear

Abstract: Postembryonic production of sensory hair cells occurs in both normal and aminoglycoside-damaged avian inner ears. The cellular source and mechanism that results in new differentiated hair cells were investigated in the avian vestibular epithelia using three distinct cell-cycle-specific labeling methods to identify proliferating sensory epithelial cells. First, immunocytochemical detection of the proliferating cell nuclear antigen, an auxiliary protein of DNA polymerase, allowed labeling of cells in late G1, S,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
1
3

Year Published

1996
1996
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 51 publications
5
60
1
3
Order By: Relevance
“…First, progenitor cells maintain a physical connection with the basal lamina during mitosis, and postmitotic cells retain a connection with the basal lamina that is permanent in the case of support cells and transient among hair cells. This hypothesis is not consistent with studies of the chick basilar papilla during development (Katayama and Corwin, 1993) and regeneration (Raphael et al, 1994;Tsue et al, 1994a), which have shown that mitotic cells are round and have no apparent connection with the basal lamina. An alternative possibility is that support cells lose contact with the basal lamina during mitosis and daughter cells migrate to more basal positions in the epithelium after mitosis.…”
Section: Mechanisms Of Hair Cell Differentiation During Regeneration contrasting
confidence: 69%
See 4 more Smart Citations
“…First, progenitor cells maintain a physical connection with the basal lamina during mitosis, and postmitotic cells retain a connection with the basal lamina that is permanent in the case of support cells and transient among hair cells. This hypothesis is not consistent with studies of the chick basilar papilla during development (Katayama and Corwin, 1993) and regeneration (Raphael et al, 1994;Tsue et al, 1994a), which have shown that mitotic cells are round and have no apparent connection with the basal lamina. An alternative possibility is that support cells lose contact with the basal lamina during mitosis and daughter cells migrate to more basal positions in the epithelium after mitosis.…”
Section: Mechanisms Of Hair Cell Differentiation During Regeneration contrasting
confidence: 69%
“…In inner ear epithelia, progenitor cell nuclei migrate from the basal lamina to the lumen during progression through the cell cycle (Ruben et al, 1971;Raphael, 1992;Katayama and Corwin, 1993;Stone and Cotanche, 1994;Tsue et al, 1994a). The temporal and spatial patterns of calmodulin expression in our study suggest that postmitotic cells also migrate from the lumen to a region below the hair cell layer before establishing their permanent location at the lumen.…”
Section: Mechanisms Of Hair Cell Differentiation During Regeneration mentioning
confidence: 57%
See 3 more Smart Citations